Pancreatic adenocarcinoma arising from heterotopic pancreas masquerading as gastritis cystica profunda - Musili Kafaru, BS; Bharti Sharma, MS; M. Maisy Meyer, BS, BA; Shaojun Liu, MD, PhD; Robert Blue, MD; George Agriantonis, MD, FACS; Jennifer Whittington, MD, PhD, FACS, FSSO; Zahra Shafaee, MD, MBA, FACS, FSSO (Radiology Case Reports)
Heterotopic pancreas is a rare, benign condition characterized by the presence of pancreatic tissue outside its normal anatomical location, and its association with malignancy is extremely rare. Gastritis cystica profunda (GCP), also a rare condition, is the cystic formation of gastric glands in the stomach submucosa and/or muscularis propria. We present the case of a 65-year-old male with who presented to the emergency department (ED) with 6 day history of worsening epigastric pain and nonbloody emesis. Computed tomography (CT) revealed gastric outlet obstruction (GOO) caused multiloculated cystic mass in the gastric antrum. Endoscopic evaluation, including esophagogastroduodenoscopy with endoscopic ultrasonography and fine needle aspiration (EGD/EUS-FNA), identified multiple cystic masses in the pylorus and duodenal bulb, which were thought to be GCP. Cytology from the EUS-FNA was benign. Carcinoembryonic antigen (CEA) of aspirated fluid was elevated to 709. The patient underwent endoscopic-guided stent placement to relieve gastric outlet obstruction and subsequent robotic partial gastrectomy. Pathological examination revealed well-differentiated invasive adenocarcinoma arising from ectopic pancreatic tissue. Postoperative imaging of the pancreas revealed no abnormalities. This case underscores the diagnostic challenges in identifying adenocarcinoma arising from heterotopic pancreas, initially misdiagnosed as GCP, and highlights the importance of considering rare causes of gastric masses in clinical practice.